Advances in anti-scale magnetic water treatment. Issue 4 (28th May 2015) - Alabi, Adetunji; Chiesa, Matteo; Garlisi, Corrado; Palmisano, Giovanni
Abstract : Water magnetic treatment provides a clean solution to handle scaling concerns. This article reports on the mechanisms and effects associated with magnetic treatment. Abstract : Scaling is the bane of households and industries that make use of water frequently. The consequences are so egregious that harmful chemicals have been sought after to remedy the situation. These chemicals, though efficacious, do more harm than good because they render water unsuitable for human consumption and cause ecological imbalance. Anti-scale magnetic water devices offer a cleaner solution to handling the scaling dilemma. This method of water treatment has been in existence for more than a century and is still the subject of much debate today, with the method being viewed with much skepticism, although evidence of its efficacy has been provided on countless occasions. Reports are given on several effects associated with magnetic water treatment, as well as proposed mechanisms. Yet no general consensus has been reached regarding the treatment method's mode of operation, which could explain the cynical reception magnetic water devices often receive. Insights into the enigmatic technique of magnetic water treatment attempt to explain magnetic effects on water and its constituents, citing explanations, which are unrelated to the current principles of magnetism. Several reports and accounts that involve the use and application of anti-scale magnetic water treatment are elucidated with special focus on calcium carbonate scale and its transformation.